Indolamine accumulation and TDC/T5H expression profiles reveal the complex and dynamic regulation of serotonin biosynthesis in tomato (Solanum lycopersicum L.) - Commisso, Mauro; Negri, Stefano; Gecchele, Elisa; Fazion, Emanuela; Pontoriero, Cecilia; Avesani, Linda; Guzzo, Flavia (Frontiers in Plant Science, 2022)
Tryptamine and serotonin are indolamines that fulfil diverse biological functions in all kingdoms of life. Plants convert L-tryptophan into tryptamine and then serotonin via consecutive decarboxylation and hydroxylation reactions catalyzed by the enzymes tryptophan decarboxylase (TDC) and tryptamine 5-hydroxylase (T5H). Tryptamine and serotonin accumulate to high levels in the edible fruits and seeds of many plant species but their biological roles in reproductive organs remain unclear and the metabolic pathways have not been characterized in detail. We identified three TDC genes and a single T5H gene in tomato (Solanum lycopersicum L.) by homology-based screening and confirmed their activity by heterologous expression in Nicotiana benthamiana. The co-analysis of targeted metabolomics and gene expression data revealed complex spatiotemporal gene expression and metabolite accumulation patterns that suggest the involvement of the serotonin pathway in multiple biological processes. Our data support a model in which SlTDC1 allows tryptamine to accumulate in fruits, SlTDC2 causes serotonin to accumulate in aerial vegetative organs, and SlTDC3 works with SlT5H to convert tryptamine into serotonin in the roots and fruits.